Incarceration, high-risk sexual partnerships and sexually transmitted infections in an urban population. Issue 1 (15th January 2012) - Rogers, Susan M; Khan, Maria R; Tan, Sylvia; Turner, Charles F; Miller, William C; Erbelding, Emily
Abstract : Objectives: The authors examined the associations between personal and partner incarceration, high-risk sexual partnerships and biologically confirmed sexually transmitted infection (STI) in a US urban population. Methods: Data from a probability survey of young adults 15–35 years of age in Baltimore, Maryland, USA, were analysed to assess the prevalence of personal and partner incarceration and its association with several measures of high-risk sexual partnerships including multiple partners, partner concurrency and current STI. Results: A history of incarceration was common (24.1% among men and 11.3% among women). Among women with an incarcerated partner in the past year (15.3%), the risk of current STI was significantly increased (adjusted prevalence ratio=2.3, 95% CI 1.5 to 3.5). Multiple partners (5+) in the past year and partner concurrency were disproportionately high among men and women who had been incarcerated or who had sexual partner(s) or who had recently been incarcerated. These associations remained robust independent of personal socio-demographic factors and illicit drug use. Conclusions: Incarceration may contribute to STI risk by influencing engagement in high-risk behaviours and by influencing contact with partners who engage in risky behaviours and who hence have elevated risk of infection.